ANALISIS SIKAP ILMIAH CALON GURU PAI DALAM PERSPEKTIF GENDER - Adi Fadli (Schemata: Jurnal Pascasarjana UIN Mataram, 2019)
The purpose of this study was to analyze the ability of the scientific attitude of PAI teacher candidates from a gender perspective. A total of 148 prospective teachers of Islamic Religious Education (PAI) as a sample in the study conducted consisted of 67 men and 81 women. The sampling technique uses a cluster random sampling technique with a cross-sectional survey research design. Research data were analyzed using t-test different test. Research data collection uses a scientific attitude questionnaire instrument and interview guidelines to obtain data on the scientific attitude of PAI teacher candidates based on gender. The results showed that the scientific attitude of PAI FITK prospective teachers of Mataram State University did not have a significant difference from a gender perspective.